2017
DOI: 10.1038/bmt.2017.194
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cell count: a reliable marker of endothelial damage in patients undergoing hematopoietic stem cell transplantation

Abstract: The physio-pathologic interrelationships between endothelium and GvHD have been better elucidated and have led to definition of the entity 'endothelial GvHD' as an essential early phase prior to the clinical presentation of acute GvHD. Using the CellSearch system, we analyzed circulating endothelial cells (CEC) in 90 allogeneic hematopoietic stem cell transplantation (allo-HSCT) patients at the following time-points: T1 (pre-conditioning), T2 (pre-transplant), T3 (engraftment), T4 (onset of GvHD) and T5 (1 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
3
35
1
Order By: Relevance
“…This finding is consistent with a previously published study, demonstrating increased endothelial injury in human skin biopsies during aGVHD. 10 Additionally, a series of clinical studies have collected supporting evidence on increased endothelial dysfunction during aGVHD, such as high numbers of circulating ECs [40][41][42][43] and elevated serum levels of the endothelial stress markers ST2, von Willebrand factor, angiopoietin 2 and thrombomodulin. 31,[44][45][46] We have previously shown that aGVHD is associated to increased angiogenesis in target organs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a previously published study, demonstrating increased endothelial injury in human skin biopsies during aGVHD. 10 Additionally, a series of clinical studies have collected supporting evidence on increased endothelial dysfunction during aGVHD, such as high numbers of circulating ECs [40][41][42][43] and elevated serum levels of the endothelial stress markers ST2, von Willebrand factor, angiopoietin 2 and thrombomodulin. 31,[44][45][46] We have previously shown that aGVHD is associated to increased angiogenesis in target organs.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce operator-induced variability, all samples were analyzed by the same laboratory technician. CEC values were calculated by a dual-platform counting method using the lymphocyte subset as reference population as previously reported ( Almici et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Biomarkers could be either: (a) diagnostic biomarker (that identifies patients at the onset of clinical disease); (b) prognostic (that identifies the likelihood of a clinical event occurrence in HCT recipients), or (c) predictive (that categorizes patients by their likelihood of response to a particular treatment when measured prior to the treatment) [2]. Since GVHD and RRTs share a common trigger, particularly damaged endothelium [5], circulating endothelial cells (CECs) have been evaluated as a diagnostic biomarker for SOS [6] and as a prognostic marker for endothelial damage [7–10], acute GVHD [7,11], and thrombotic microangiopathy (TMA) [12]. Similarly, regulatory T cells (Tregs) [13], CD146 + T cells [14] and invariant natural killer T cells [15] have been evaluated as diagnostic/prognostic biomarkers for acute GVHD.…”
Section: Introductionmentioning
confidence: 99%